Effect of surface electrode recording area on compound muscle action potential scan processing for motor unit number estimation - Zhang, Dan; Lu, Zhiyuan; Gong, Weijun; Zhou, Ping (Frontiers in Neuroscience, 2024)
Introduction: MScanFit is a model-based algorithm for motor unit number estimation (MUNE) from compound muscle action potential (CMAP) scan data. It is a clinically applicable tool because of its quick and automatic implementation. Electrodes with different recording areas were employed to record CMAP scan data in existing studies. However, the effect of electrode recording area on MScanFit MUNE and other CMAP scan parameters has not been studied. Methods: CMAP scan was performed on the abductor pollicis brevis muscle of both hands on fourteen healthy subjects using three different electrodes with recording areas of 10 mm × 10 mm, 11 mm × 14 mm, and 22 mm × 26 mm, respectively. Motor unit number was estimated using MScanFit for each CMAP scan. Two motor unit number index parameters, i.e. D50 and step index (STEPIX), were also derived from the CMAP scan data. Results: No significant difference in D50, STEPIX, and MScanFit MUNE was observed across three different electrode recording areas, although the amplitude of CMAP decreased significantly when a larger electrode was used. Intraclass correlation coefficients of 0.792 and 0.782 were obtained for MScanFit MUNE and STEPIX, respectively. Discussion: Compared with CMAP amplitude, D50, STEPIX, and MScanFit MUNE are less sensitive to variation in electrode recording area. However, the repeatability of MScanFit MUNE could be compromised by the inconsistency in the electrode recording area.